Una experiencia de aplicación de Realidad Aumentada para el Aprendizaje del Inglés en Educación Infantil - Aguirregoitia Martínez, Amaia (2020)
The current study presents an educational experience using augmented reality technology which aims to improve vocabulary acquisition and grammatical structures in English while introducing curricular contents of emotional intelligence in a CLIL approach. The presented Didactic Unit incorporates Augmented Reality activities to encourage autonomous learning through exploration which also include self-evaluation. The proposal incorporates images and audio to facilitate content learning and introduce phonetics from the Infant Education stage using narrations and songs. The evaluation that has taken place in six different classrooms points out a very positive acceptance of the methodology by the students. Besides, the learning results have significantly improved, which may be, to some extent, related to the used methodology.